TECHNICAL EFFICIENCY AND PRODUCTION SCALE ANALYSIS IN SMALL-SCALE TUNA HANDLINE FISHERIES IN WEST SULAWESI - Hatmar, Muh Aldhy; Nelwan, Alfa (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
Tuna fishing activity in West Sulawesi has intensified in recent years, raising concerns regarding the sustainability of the fishery in the Makassar Strait amid increasing fishing pressure. This study evaluates the capacity utilization and resource use efficiency of small-scale handline vessels by measuring their technical and scale efficiency. A total of 78 tuna handline vessels were analyzed using an output-oriented Data Envelopment Analysis (DEA) model under Variable Returns to Scale (VRS), covering two vessel categories: <5 GT and 5–10 GT. Vessel samples were selected through stratified random sampling from the Banggae and Tinambung sub-districts. The results show that vessels in the 5–10 GT category exhibit higher technical efficiency in utilizing production inputs and fishing capacity, while vessels smaller than 5 GT tend to operate closer to the optimal scale, with most exhibiting increasing returns to scale (IRS). These findings highlight that efficiency improvements in the small-scale segment could be achieved through targeted technological assistance and training, particularly among smaller vessels (<5 GT), while capacity management remains essential in larger vessels (5–10 GT) to prevent excessive fishing effort. Integrating efficiency-based management insights with Indonesia’s Measured Catch Policy is critical to support the sustainability of tuna fisheries in the region. Keywords: DEA, scale efficiency, small-scale fisheries, tuna fishing, technical efficiency